Textiles and Social Status. The Case of Late Medieval Elbląg - Anna Rybarczyk (Fasciculi Archaeologiae Historicae, 2018)
High quality textiles were unquestionably one of the most luxurious goods in the Middle Ages. Expensive fabrics, especially silks are recognised as indicators of the owner’s high social status. The excavations conducted in Elbląg (Elbing) gave rise to a very interesting collection of textiles. The fact that most of these finds came from parcels with well-known historical background offers a rare opportunity to relate the discovered textiles to their owners. It is also possible to link certain types of fabrics mentioned in written sources to actual archaeological finds. Combining archaeological and historical data enables us to shed some light on the question of using expensive textiles by townspeople in a late medieval Hanseatic town. A great correspondence of these sources as far as textile evidence is concerned can be observed: types of textiles listed in the sumptuary laws were successfully identified in the excavated evidence.